Developing an experimental paradigm for the study of loot boxes - Hancock, Patrick McMillen (My University, 2025)
Loot boxes are lucrative random reward systems prominently featured in the modern video game industry. Psychological research on loot boxes has relied primarily on self-report correlational studies, which have found concerning similarities between loot boxes and gambling that warrant further study in an experimental paradigm. However, loot boxes may also serve as a model to better understand human operant conditioning, which often fails to replicate the results of animal learning studies. In pursuit of both of these goals, we drew from the cognitive decision-making and operant conditioning literature to develop an experimental paradigm for the study of loot boxes. In two experiments, the paradigm was used to investigate how different reinforcement schedules (fixed-ratio, variable-ratio, and random-ratio) and schedule variability (Study 1), as well as variable reinforcement magnitude (Study 2), influenced players' decisions to open loot boxes. Participants in Study 1 initially opened loot boxes more on highly variable schedules, but the effect was short-lived. Study 2 found no effects of variable magnitude on loot box opening decisions. Although we failed to find support for any of our hypotheses, we discuss a number of modifications that can be made to the paradigm in future studies.
Keywords: Loot boxes; Gambling; Ratio schedules of reinforcement; Variable reinforcer magnitude